Penyemaian Sikap Hidup Damai di Sekolah: Tinjauan Pendidikan Perdamaian dan Multi-Dimensi Kurikulum - Nurwanto Nurwanto; Wahdan Najib Habiby (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This article aims to theoretically elaborate a strategy of disseminating peace through peace education and curriculum construction integrated with schooling experiences. Violent behaviors committed by several groups of students have become a reason of why peace dissemination in schools is paramount. The existing curriculum merely concerning its teaching and learning documents has been considered as both insufficient for integrated peace education and inadequate to transform behaviors for peace. This study was conducted through library research on books and journals informing peace education and multidimensional curriculum. This study finds that peace education, which includes building capacities to reduce violence and to sustain cooperative and equal relationships, can be constructed in schooling processes. Moreover, the learning stages need to incorporate various dimensions of peace contents or experiences as planned, acted, evaluated, learned and hidden within the classroom and school interactions. It is suggested that the multi-dimensional curriculum is likely to cohere with a comprehensive school framework for peaceful school life.